PENINGKATAN PENGETAHUAN KADER KESEHATAN DALAM MANAJEMEN ASIP DI DUSUN AWISARI CIKONENG CIAMIS - Dewi Aryanti; Tetik Nurhayati; Iwan Somantri (Edukasi Masyarakat Sehat Sejahtera (EMaSS) : Jurnal Pengabdian kepada Masyarakat, 2023)
Expressed breastmilk (ASIP) is one attempt to successfully support exclusive breastfeeding. Exclusive breastfeeding remains an important activity, especially during the COVID-19 pandemic, which is beneficial for the baby's endurance, mother's health and happiness. The purpose of this public service activities was provided refreshment to the health worker in the village dusun Cikoneng Awisari Cikoneng Ciamis of the ASIP management. The methods used are workshops and counseling. Infrastructure required was counseling room (Rumah Dataku dusun Cikoneng), phantom breast pocket books, videos milking the milk manually and using the pump, infokus, and speaker stuffs. The results of activities was increasing the knowledge of health workers in ASIP management during the COVID-19 pandemic. Outputs from this activity is the publication of the results of community service and booklets ASIP